MTP Beyond 20th Week of Gestation: A Rare Case of Anencephaly (Indian Internet Journal of Forensic Medicine and Toxicology, 2017)
Various rights of woman have been recognised under Indian Constitution and case laws pronounced by the Hon’ble Supreme Court of India from time to time. The Hon’ble Supreme Court of India observed that a woman’s right to make reproductive choices is also a dimension of ‘personal liberty’ as understood under Article 21 of the Constitution of India in the case of Suchita Srivastava and Anr. vs. Chandigarh Administration (2009). The crucial consideration is that a woman’s right to privacy, dignity and bodily integrity should be respected. This means that there should be no restriction whatsoever on the exercise of reproductive choices such as a woman’s right to refuse participation in sexual activity or alternatively the insistence on use of contraceptive methods. Women are also free to choose birth-control methods such as undergoing sterilisation procedures. Taken to their logical conclusion, reproductive rights include a woman’s entitlement to carry a pregnancy to its full term, to give birth and to subsequently raise children. A rare case of anencephaly was filed before the Supreme Court [SC] in which pregnancy crossed beyond the 20th week of gestation, permissible limit under the Medical Termination of Pregnancy (MTP) Act, 1971. Various facets of woman’s rights, like consent, right to privacy, bodily integrity and so on, have been discussed by the Division Bench of the SC. This is a first case of anencephaly from India where MTP was allowed by the Apex Court of India where pregnancy crossed 20 weeks of gestation.
Keywords: Anencephaly; Consent; Medical board; Mental health; MTP; Physical health; Reproductive autonomy